2020
DOI: 10.1111/nep.13804
|View full text |Cite
|
Sign up to set email alerts
|

Asian Pacific Society of Nephrology Clinical Practice Guideline on Diabetic Kidney Disease – An Executive Summary

Abstract: In the 2018 iteration of the United States Renal Data System (USRDS) report, 6 out of the top 10 countries in the world with diabetic kidney disease (DKD) as the cause of end-stage kidney disease (ESKD) were from the Asia-Pacific region, with Malaysia and Singapore topping the charts consistently over the previous years (1). It is, therefore, unsurprising that DKD is a significant healthcare burden for the Asia-Pacific countries, with a considerable amount of the countries' medical expenditure being spent on k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…We separated the biopsy details and clinical features at the presentation of the patients on the electronic records of the hospital information system of this public sector tertiary care institute. All patients had standard indications for biopsies, i.e., absence of retinopathy, presence of active sediments, red blood cells/cast in urine, heavy proteinuria on first presentation and sudden deterioration in degree of proteinuria, rapid decline in GFR as per standard guidelines [ 8 , 9 ]. Patients with Type-1 DM and pregnant and lactating females were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…We separated the biopsy details and clinical features at the presentation of the patients on the electronic records of the hospital information system of this public sector tertiary care institute. All patients had standard indications for biopsies, i.e., absence of retinopathy, presence of active sediments, red blood cells/cast in urine, heavy proteinuria on first presentation and sudden deterioration in degree of proteinuria, rapid decline in GFR as per standard guidelines [ 8 , 9 ]. Patients with Type-1 DM and pregnant and lactating females were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…13,17 Because of the complex aetiology of renal disease in conjunction with type 2 diabetes, the broader term 'diabetes kidney disease' is now preferred. 18 In the Pasifika population, obesity-related focal segmental glomerulosclerosis is the commonest non-diabetic renal disease and like classical diabetic nephropathy, with which it can co-exist, it is characterised by macroalbuminuria, a bland urine sediment and progressive loss of renal function. In the population, we describe 29% of people with type 2 diabetes and macroalbuminuria had no retinopathy at the time the latter was recogniseda similar proportion to our findings in an earlier study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, albumin is essential in plasma for maintaining the osmotic pressure of the blood [ 3 ]. Albumin levels are clinically useful in assessing liver function, kidney function, and nutritional status [ 4 ]. A retrospective study showed that hypoalbuminemia in patients with coronavirus disease 2019 was associated with illness progression to more severe stages and increased mortality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%